Development of an Aptamer-Based Electrochemical Biosensor for Early Detection of Prostate Cancer Markers - Lim, Sofia; Tan, Marcus; Tan, Ethan (Yayasan Adra Karima Hubbi, 2024)
Prostate cancer is a leading malignancy in men, where early detection is critical for effective treatment. Current diagnostic methods, such as PSA tests, have limitations in sensitivity and specificity. To develop an aptamer-based electrochemical biosensor for the early detection of prostate cancer markers, aiming to improve diagnostic accuracy and speed. The study involved the design and optimization of aptamers through SELEX, integration with electrochemical sensors, and validation using prostate cancer cell lines and clinical samples. Instruments used include electrochemical workstations, HPLC, and mass spectrometry for characterization and evaluation. The developed biosensor demonstrated a detection limit of 0.1 ng/mL for PSA, with a response time of less than 10 minutes. High reproducibility was achieved with a coefficient of variation below 5%, and the biosensor showed significant specificity and stability in detecting PSA in various samples. The aptamer-based electrochemical biosensor offers a promising tool for the early detection of prostate cancer markers, providing higher sensitivity and specificity compared to traditional methods. Further clinical validation is necessary to confirm its efficacy and reliability in broader applications.